Growth and Yield of Cassava in Agro Forestry System Using Crown Tree Management: Crown Pruning for Optimization Light Interception - Mofit Saptono; Hastin Ernawati N.C.C. (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
The aim of this research is to measure the light intensity change under the tree due to the change of crown tree density in agro forestry system. The factorial completely randomized block design with four replications was applied on this research. The first factor were species in agro forestry system namely: mahagony (Switenia mahagony), teak (Tectona grandis), para-serianthes (Paraserianthes falcataria) and mangium (Acacia mangium). The age of the species mentioned above is five years old. Second factor were crown tree pruning including; without pruning (0%), pruning 50%, and pruning 75%. The result showed that the light intensity in open area is 1150 μmole m-2 sec-1.The average of light intensity under the crown tree of mahagoni, teak, paraserianthes and mangium were 830, 607, 443 and 403 μmole m-2sec.-1, respectively. The light intensity under the tree without pruning was 497 μmole m-2 sec-1, whereas with 50% and 75% of pruning increased light intensity up to 554 and 661 μmole m-2 sec.-1, respectively. Cassava tuber yield in agro forestry system were 5.4; 3.2; 3.7 and 1.2 Mg ha-1 respectively under mahagony, teak, paraserianthes and mangium, respectively. The yield of cassava in agro forestry system was lower than monoculture system (26.9 Mg ha-1). Keywords: crown tree, mahagony, teak, paraserianthes, mangium, cassava, agroforestry system